Dynamics of Magnetization in Multilayer TbCo / FeCo Structures under the Influence of Femtosecond Optical Excitation - N. A. Ilyin; A. A. Klimov; N. Tiercelin; P. Pernod; E. D. Mishina; M. S. Gaponov; K. A. Brekhov; A. S. Sigov; V. L. Preobrazhensky (Российский технологический журнал)
The need to study ultrafast processes in magnetism is due to the prospects for creating ultrafast magnetic recording and ultrafast spintronic devices. In order to excite the magnetic subsystem femtosecond optical pulses are used. The excitement is manifested as in spin precession. In metals, the material is heated first due to significant optical absorption, and significant Joule losses occur. The most important task is to search for materials in which spin processes are excited without heating. Obvious candidates are weakly absorbing materials, such as ferrite garnets. However, the range of such materials and the range of their functionality are limited.The purpose of this work is to study the dynamics of systems with nonthermal mechanisms of spin precession excitation. Such excitation is possible in ferromagnetic / antiferromagnetic heterostructures with exchange interaction, provided that the recombination time of photocarriers is shorter than the time of heat diffusion. Multilayer TbCo / FeCo structures of the near IR range were investigated for a femtosecond optical pulse. The spin dynamics are compared with the direction of the wave vector of the exciting pulse along and perpendicular to the axis of easy magnetization of the structures (“easy axis” and “hard axis” geometry, respectively). It is shown that in case of “easy axis” geometry the determinative mechanism is the thermal interaction. When the system is exposed to an excitation pulse, this mechanism leads to a decrease in the projection of magnetization on the direction of propagation of the test beam. In case of “hard axis” geometry, the magnetization turns to the magnetic field at the initial stage. Then it precesses and relaxes to an equilibrium angular orientation. Such dynamics indicate a rapid recovery of the uniaxial anisotropy field after laser irradiation. The presented results demonstrate an ultrafast change in the magnetic anisotropy induced during the fabrication of the heterostructure under study, which may be of interest for optical control of the orientation of the magnetization.